UPAYA HUKUM ATAS PENENTUAN NILAI LIMIT LELANG OLEH BANK DI BAWAH HARGA PASAR - Rahmadi Indra Tektona; Ulhfah Mutiarachmah (Fakultas Hukum Universitas Islam Malang, 2021)
he limit value was a key part in the auction. The bank was as a seller who would determine auction limit value which was based on the assessor’s assessment and evaluator’s estimation ruled in the article 44 paragraph (1) and (2) and the article 45 of Minister of Finance’s Regulation 27/PMK.06/2016 on the instructions of auction. The problem was whether the auction cancellation could be performed based on the limit value determination below the market price? Second, what were the legal efforts which could be attempted by the debtor when the auction limit value determination from bank was under the market price? This research was a juridical normative research. Based on the research finding, the researcher drew a conclusion that the determination of auction limit value below the market price could not be a base of auction cancellation on pre-auction stage and auction stage, since the auction cancellation could only be cancelled upon the seller’s request or based on court’s decision or sentence. Furthermore, the debtor who might feel harmed over the auction limit value determination could do some legal efforts to file a lawsuit.